Heat stress tolerance in maize - An overview - Hemaswi , S; Kumari , VN; Sivakumar , S; Vanitha , K; Kathirvelan , P (Plant Science Today, 2025)
Maize (Zea mays L.), one of the world’s most important staple crops, is increasingly vulnerable to rising temperatures and erratic climatic conditions. Among various abiotic stressors, heat stress stands out as a critical factor that disrupts the crop’s growth by impairing morphological, physiological, biochemical and molecular processes ultimately leading to substantial yield losses. The severity of this issue is expected to escalate with the intensification of global warming and water scarcity. To ensure sustainable maize production, there is an urgent need to develop heat-resilient, high-yielding hybrids. This review explores recent advances in identifying thermotolerant donor lines and employing them in hybrid development. Emphasis is placed on integrated strategies, including advanced agronomic interventions, molecular breeding, CRISPR/Cas-based genome editing and the application of multi-omics platforms transcriptomics, proteomics, metabolomics and phenomics to decipher heat-responsive mechanisms. Furthermore, the integration of high-throughput phenotyping, machine learning and climate-smart agricultural practices offers promising pathways to accelerate breeding efficiency and improve field-level adaptation. By synthesizing these cutting-edge approaches, this review provides a comprehensive framework to mitigate the adverse impacts of heat stress and support climate-resilient maize cultivation in the face of future challenges.